2002
DOI: 10.1016/s0014-5793(02)03059-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitration of PPARγ inhibits ligand‐dependent translocation into the nucleus in a macrophage‐like cell line, RAW 264

Abstract: Nitration of tyrosine residues in proteins has been observed in many in£ammatory tissues of arthritis, ulcerative colitis, septic shock and ischemia-reperfusion injury. Although several studies have been carried out, it is still unclear what type of protein is nitrated and whether tyrosine nitration interferes with protein function. Peroxisome proliferator-activated receptor gamma (PPARQ Q) is a nuclear receptor whose activation is linked to several physiological pathways including regulation of insulin sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 25 publications
3
44
1
1
Order By: Relevance
“…44 For example, peroxisome proliferator-activated receptor gamma expression protects neurons from Abmediated toxicity; 45 however, its nitration prevents its translocation to the nucleus, thereby preventing mitochondrial biogenesis. 46 We also found that nanoceria blocked Ab-mediated mitochondrial fragmentation via a mechanism that involved reduction of DRP1 S616 hyperphosphorylation (Figure 5b). Although it is unlikely that nitrosative stress mediates mitochondrial fragmentation and neuronal cell death only by phosphorylation of a single protein target, such as DRP1, our data describe one possible pathway by which nanoceria can attenuate the downstream effects of RNS/ROS.…”
Section: Discussionmentioning
confidence: 60%
“…44 For example, peroxisome proliferator-activated receptor gamma expression protects neurons from Abmediated toxicity; 45 however, its nitration prevents its translocation to the nucleus, thereby preventing mitochondrial biogenesis. 46 We also found that nanoceria blocked Ab-mediated mitochondrial fragmentation via a mechanism that involved reduction of DRP1 S616 hyperphosphorylation (Figure 5b). Although it is unlikely that nitrosative stress mediates mitochondrial fragmentation and neuronal cell death only by phosphorylation of a single protein target, such as DRP1, our data describe one possible pathway by which nanoceria can attenuate the downstream effects of RNS/ROS.…”
Section: Discussionmentioning
confidence: 60%
“…Third, suppression of COX-2 activity by NS-398, inhibition of PPAR-g by GW9662 as well as knockdown of COX-2 and PPAR-g by siRNA led to profound reductions of both cannabidiol's proapoptotic and cytotoxic action. Fourth, immunocytochemical analyses of the subcellular compartimentalization of PPAR-g revealed a significant cannabidiol-induced accumulation of PPAR-g within nuclear regions that has been described as marker of PPAR-g activation (32). This effect was mimicked by PGD 2 , 15d-PGJ 2 , and troglitazone and inhibited by NS-398 indicating an involvement of cannabidiol-induced COX-2 activity in PPAR-g activation.…”
Section: Discussionmentioning
confidence: 87%
“…The impact of phosphorylation on the activity of PPARs depends on the residue being phosphorylated, and the kinase cascade that has been activated ; nitration of tyrosine residues in PPARγ inhibits the translocation from the cytosol to the nucleus (Shibuya et al, 2002). Ligand binding to PPARγ induces ubiquitilation (Hauser et al, 2000), and therefore receptor degradation, while ligand binding to PPARα stabilizes the receptor by decreasing its rate of ubiquitilation (Blanquart et al, 2002).…”
Section: Insidementioning
confidence: 99%